Grounding Urban Natures Histories and Futures of Urban Ecologies - Ernstson, Henrik; Sörlin, Sverker (Urban and Industrial Environments, 2019)
Case studies from cities on five continents demonstrate the advantages of thinking comparatively about urban environments. The global discourse around urban ecology tends to homogenize and universalize, relying on such terms as "smart cities," "eco-cities," and "resilience," and proposing a "science of cities" based largely on information from the Global North. Grounding Urban Natures makes the case for the importance of place and time in understanding urban environments. Rather than imposing a unified framework on the ecology of cities, the contributors use a variety of approaches across a range of of locales and timespans to examine how urban natures are part of-and are shaped by-cities and urbanization. Grounding Urban Natures offers case studies from cities on five continents that demonstrate the advantages of thinking comparatively about urban environments. The contributors consider the diversity of urban natures, analyzing urban ecologies that range from the coastal delta of New Orleans to real estate practices of the urban poor in Lagos. They examine the effect of popular movements on the meanings of urban nature in cities including San Francisco, Delhi, and Berlin. Finally, they explore abstract urban planning models and their global mobility, examining real-world applications in such cities as Cape Town, Baltimore, and the Chinese "eco-city" Yixing. Contributors Martín Ávila, Amita Baviskar, Jia-Ching Chen, Henrik Ernstson, James Evans, Lisa M. Hoffman, Jens Lachmund, Joshua Lewis, Lindsay Sawyer, Sverker Sörlin, Anne Whiston Spirn, Lance van Sittert, Richard A. Walker